2019
DOI: 10.31557/apjcp.2019.20.10.2943
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Potential of Petroleum ether, Ethyl Acetate, Chloroform, and Ethanol Extracts of Lavandula Coronopifolia Against Human Breast Carcinoma Cell line (MDA-MB-321)

Abstract: Background: Breast cancer is the most common cause of deaths in women. The search for traditionally used medicinal plants which can serve as non-toxic and affordable anticancer drugs is the need of the hour. This study aimed to investigate the anticancer potential of extracts of L. coronopifolia against human breast carcinoma cell line (MDA-MB-321). Methods: The MDA-MB-231 cells were plated in 96 well plates and exposed to 10-1,000 µg/ml of L. coronopifolia for 24 h. The cytotoxic response of different extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Natural plant species have been used not only as sources of food, but also as remedies for many diseases in the ancient era. Different reports suggested that there are unidentified properties in different parts of plants that can be used in the treatment of certain diseases [ 6 ]. The current investigation intended to reveal the potential anticancer and anti-proliferative activities of lavender plant extracts in liver cancer cell line in an in vitro model.…”
Section: Introductionmentioning
confidence: 99%
“…Natural plant species have been used not only as sources of food, but also as remedies for many diseases in the ancient era. Different reports suggested that there are unidentified properties in different parts of plants that can be used in the treatment of certain diseases [ 6 ]. The current investigation intended to reveal the potential anticancer and anti-proliferative activities of lavender plant extracts in liver cancer cell line in an in vitro model.…”
Section: Introductionmentioning
confidence: 99%
“…Widiyastuti et al [39] reported that the ethanolic extracts (flowers, stems and leaves) of Stachytarpheta jamaicensis (L.) Vahl had no toxic effect on HeLa cells. On the contrary, Al-Sheddi et al [40] reported the cytotoxic effect of ethyl acetate, chloroform and ethanol extracts of Lavandula coronopifolia against MDA-MB-321 cells and in the same vein, the crude leaves ethanol extract of Lasiosiphon eriocephalus exhibited a high toxicity effect against HeLa cells [41]. In vitro cytotoxicity studies revealed that ethanol extracts of leaves of Tamilnadia uliginosa exhibited toxic effects on HeLa cells [42].…”
Section: Biocompatibility Studymentioning
confidence: 99%